The Effect of the Role-Playing Learning Model on Grade V Students’ Speaking Skills at IT Zia Salsabila Elementary School - Masnuripa Siregar; Sahkholid Nasution (Sakura Digital Nusantara, 2026)
This research was conducted due to the low speaking ability of elementary school students in Indonesian language subjects. Some students still lack confidence in speaking, have difficulty expressing their opinions, and are less active in learning activities due to the use of learning methods that are still lecture-based and teacher-centered. This study aims to analyze the effect of the role-playing learning model on the speaking skills of fifth-grade students of SD Swasta IT Zia Salsabila. This study used a quantitative method with a One Group Pretest-Posttest design involving 20 students as research subjects. Data on speaking skills were obtained through practical tests and then analyzed using paired sample t-tests through SPSS software. The results of the study showed a significant increase in students' speaking skills, with the average pretest score increasing from 12.25 to 22.35 at the time of the posttest. The results of statistical tests with a significance value of 0.000 <0.05 proved that the role-playing model was very effective in improving speaking skills and building students' courage to participate actively. which shows that the role-playing model had a significant effect on students' speaking skills. The application of this model was also able to increase students' participation, courage, and confidence in the communication process. Therefore, teachers are advised to apply the role playing learning model as a creative, interactive, and effective learning strategy in improving elementary school students' speaking skills.